Narasi Digital dan Keputusan Finansial: Tinjauan Sistematis tentang Pengaruh Media Sosial terhadap Perilaku Investor dan Analis Keuangan - Fatimah Akbal (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Social media has emerged as a major channel for disseminating financial information, significantly influencing how investors and financial analysts make investment decisions. This study aims to identify and synthesize scientific findings on the impact of social media-based financial content on investment behavior through a Systematic Literature Review (SLR) of 71 Scopus Q1-indexed articles published between 2015 and 2025. The analysis reveals that social media not only accelerates information flow but also shapes risk perceptions, triggers behavioral biases such as herding, overconfidence, and confirmation bias, and shifts informational authority from professional analysts to informal actors like finfluencers. While it offers opportunities for democratizing financial information and increasing retail investor engagement, it also raises serious concerns over content credibility, validity, and the gap in financial literacy. The study further highlights research gaps in areas such as analyst behavior, policy effectiveness, cross- country comparisons, and the application of technologies like natural language processing (NLP) in sentiment analysis. Theoretically, the findings extend behavioral finance and signaling theory into the digital context, while practical implications suggest the need for ethical, data-driven, and context-sensitive digital financial communication design. This review encourages future interdisciplinary research and evidence-based policy development in response to the growing complexity of today’s digital financial.